2018
DOI: 10.1111/gcb.14311
|View full text |Cite
|
Sign up to set email alerts
|

The “isohydric trap”: A proposed feedback between water shortage, stomatal regulation, and nutrient acquisition drives differential growth and survival of European pines under climatic dryness

Abstract: Climatic dryness imposes limitations on vascular plant growth by reducing stomatal conductance, thereby decreasing CO uptake and transpiration. Given that transpiration-driven water flow is required for nutrient uptake, climatic stress-induced nutrient deficit could be a key mechanism for decreased plant performance under prolonged drought. We propose the existence of an "isohydric trap," a dryness-induced detrimental feedback leading to nutrient deficit and stoichiometry imbalance in strict isohydric species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 81 publications
4
65
0
Order By: Relevance
“…the 'isohydric trap' feedback loop in European Pines found that strong stomatal regulation led to a series of physiological changes (detected for example using carbon isotope abundance) that ultimately culminate in a severe mineral nutrient imbalance and reduced ability to tolerate drought stress. While some of the results described by Salazar-Tortosa et al (2018) were similar to the findings in this study for leaf and phloem tissue, we demonstrate that the investment in reproductive tissue, particularly important for crop species, overrides any concern for a long term feedback loop as was observed in European Pines. Fig.…”
Section: Figuresupporting
confidence: 87%
See 2 more Smart Citations
“…the 'isohydric trap' feedback loop in European Pines found that strong stomatal regulation led to a series of physiological changes (detected for example using carbon isotope abundance) that ultimately culminate in a severe mineral nutrient imbalance and reduced ability to tolerate drought stress. While some of the results described by Salazar-Tortosa et al (2018) were similar to the findings in this study for leaf and phloem tissue, we demonstrate that the investment in reproductive tissue, particularly important for crop species, overrides any concern for a long term feedback loop as was observed in European Pines. Fig.…”
Section: Figuresupporting
confidence: 87%
“…Despite detecting a higher nutrient content in well‐watered compared to water deficit treatment plants, the results were variable, therefore no statistically significant differences for any nutrients or amino acids were found in response to treatment or development stage within the soluble leaf, soluble and total pod pools. The recent work of Salazar‐Tortosa et al () describing the ‘isohydric trap’ feedback loop in European Pines found that strong stomatal regulation led to a series of physiological changes (detected for example using carbon isotope abundance) that ultimately culminate in a severe mineral nutrient imbalance and reduced ability to tolerate drought stress. While some of the results described by Salazar‐Tortosa et al () were similar to the findings in this study for leaf and phloem tissue, we demonstrate that the investment in reproductive tissue, particularly important for crop species, overrides any concern for a long term feedback loop as was observed in European Pines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinus halepensis, P. pinea and to a lesser extent P. pinaster are less frost-tolerant than the high-mountain pines P. sylvestris and P. nigra (Climent et al 2009;Fernández et al 2017;Toca et al 2017). However, the fact that P. sylvestris and P. nigra do not occur at low-altitude locations where summers are dry and hot could be explained by a lower capacity to survive water stress than Mediterranean pines in the early life stages (Salazar-Tortosa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Larger pine seedlings (both within and across years) likely had a larger root system, which would have reduced competition with the shallow root system of most forbs and grasses [5]. In addition, nutrient acquisition by the pine seedlings may improve with better access to soil water [5,53], thereby reinforcing the positive effect of a larger size.…”
Section: Discussionmentioning
confidence: 99%